The predictive power of sociobiographical and language variables on foreign language anxiety of Chinese university students. (April 2020) - Jiang, Yan; Dewaele, Jean-Marc
Abstract: A large majority of studies have been conducted on foreign language anxiety (FLA) in the context of the classroom where interlocutors are teacher and peers, whereas fewer researchers have examined FLA beyond the confines of the classroom. The present study examined 1, 031 Chinese university students' FLA in English and explored the links between it and several sociobiographical variables (i.e. gender, ethnic group affiliation, geographical background, and experience in travelling abroad) and language variables (i.e. age of onset of acquisition, language achievement level, self-perceived oral competence, and frequency of language use). The results showed that geographical background, experience abroad, age of onset of acquisition, self-perceived oral competence, language achievement level, and frequency of language use were significantly linked with FLA. The findings suggest that FLA exists as much outside as inside the classroom but that the sources vary and that the nature of the experience may change as individuals outside the classroom have a greater sense of agency. The study also offers some pedagogical implications for Chinese EFL teachers.